INTERCULTURAL APPROACH IN ENGLISH AS A FOREIGN LANGUAGE TEACHING AT HIGHER INSTITUTION - Korenetskaya, Irina; Semenova, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article studies and analyses interculturality in ELT by means of intertextuality.The main focus of this paper is onthe integration of an intercultural approach in the content of modern academic curricula, as well as the intertextual features of texts in a foreign language classroom. The precedent texts, representing the phenomenon of intertextuality, developinterculturality in education via reflexive understanding of the Self and the Other on the border of cultures and values. Thus, the concepts of “intertextuality” and “interculturality” are analyzed in this article, their interrelation is shown, some ways of understanding of the precedent texts and implementation of interculturality in ELT are offered.The article focuses on the linguistic features of educational texts, not so much on the traditional and stereotyped cultural and value differences between the representatives of different nationalities, which leads to the establishment of barriers in interpersonal interaction, but rather on the cultivation of similarity, acceptance of cultural diversity, and awareness of Self and one's own identity.There are many effective ways to develop intercultural skills, applying such methods as CLIL, case-study, role-plays, lapbooking, projects. The conclusion reflects the main results of the research, revealing the essence of transformations of precedent texts, which form the students’ image of the world and affect the addressee in the way, necessary for the addresser.